Student Mobility and the Internationalization of Higher Education: National Policies and Strategies from Six World Regions (A Project Atlas Report) - Sharma, Ghanashyam (Journal of International Students, 2012)
The Institute of International Education’s Project Atlas Report (2011) shows that the overall context of international students’ movement has been changed in the past few years. Policies and strategies adopted by new host countries and their academic institutions and organizations are changing the patterns of international students’ mobility. New players are redefining the field by influencing which international students want to go where and why.